16.2: Invited Paper: Evaluate the Repeatability and Reliability of Heterophoria Measurement Based on Display. (24th February 2021) - Zheng, Fuhao; Chen, Bingzhen; Huang, Pingping; Mei, Jianhui; Chen, Yuanyuan; Chen, Shuang; Hou, Fan; Chen, Hao; Wang, Yuwen
Abstract : Objective: To design a Heterophoria Test based on Display (DHT) for clinical work, and evaluate its reliability, repeatability and validity. Methods: We recruited 30 students (9 males, 21 females, Age 24.62±2.65), from Wenzhou Medical University, randomly, excluding high myopia, strabismus, anisometropia, eye disease and history of ophthalmological surgery, to preform two experiments. The first one is that we use DHT, Von Graefe test (VG), modified Thorington test (MT), Maddox rod test (MR), and Prism‐neutralized objective cover test (POCT) to detect heterophoria for near(0.33m), middle(0.77m) and far distance(3m). We use ICC and Bland‐Altman Analysis to evaluate repeatability and reliability of DHT. The second is that we use DHT to detect the change of phoria before and after 20‐minute prism adaptation for middle distance (0.77m), to evaluate the validity of DHT "Fig. 1". Results: In the first experiment, the result of DHT has no statistic difference with MT, MR, and POCT( p >0.05). the result of VG has statistic difference with other measurements and shows more exophoria for far distance. There is no statistic difference among DHT, MR and POCT for middle distance. Except the result of DHT and POCT, MT and MR, having no statistic difference( p >0.05). Results of other methods are different with each other( p >0.05). ICC, mean difference and 95%LoA between DHT and MT, MR, VG, POCT for different distance are shown in Table 1. In terms to repeatability, ICC for 7 times measurement are 0.99, 0.97, 0.97 for far, middle and near distance, respectively. ICC, Mean difference and 95%LoA are shown in Table 1, too. In the second experiment, Heterophoria before prism adaptation has statistic difference with that after adaptation ( t =5.016, p <0.001), compared with Karpicka's study using MT to detect the heterophoria difference (1) "Fig. 2". Conclude: DHT has fairly remarkable repeatability and reliability for far and middle distance. It is more userfriendly than MT, VG, POCT and MR. But the reliability of near measurement should improve in the future.